Two decades of childhood cancer care in Cameroon: 2000–2020. Issue 7 (15th March 2021) - Afungchwi, Glenn Mbah; Kruger, Mariana; Kouya, Francine; Tih, Pius; McCormick, Peter; Pondy‐Ongotsoyi, Angele‐Hermine; Hesseling, Peter B.
Abstract: Background: Before the year 2000, there was no dedicated childhood cancer service in Cameroon. The aim of this study was to investigate the progress made with pediatric oncology care in Cameroon from 2000 to 2020. Method: A literature search was conducted for published articles on childhood cancer in Cameroon and relevant documents, and conference abstracts were reviewed. The articles were analyzed under the themes: awareness, diagnosis, epidemiology, treatment, outcome, advocacy, partnerships, traditional and complementary medicine, palliative care, and capacity building. Results: Low awareness on childhood cancer was addressed with education activities targeting the general population and health care professionals. Cancer diagnosis was achieved with cytology, histology, and simple imaging. Management for common and curable cancers was implemented with use of modified treatment regimens for low‐ and middle‐income settings. Nutritional support was shown to mitigate the effects of malnutrition on treatment toxicity, and support was provided for transportation and accommodation. There was good collaboration between the pediatric oncology professionals nationally and twinning with international partners. Capacity building activities led to the availability of three pediatric oncologists and pediatric oncology‐trained nurses. Advocacy nationally led to the support of the Ministry of Health with pediatric oncology‐specific priority actions in the latest national cancer control plan. Conclusion: Childhood cancer should receive the necessary attention of health care policymakers in Cameroon. With continued commitment of government, nongovernmental organizations, charities, childhood cancer specialists, patient and parent groups, there should be an improved future for children with cancer in Cameroon.